FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MANAJEMEN LABA STUDI PADA PERUSAHAAN FOOD AND BAVERAGE - Roudhotul Maksumah (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2020)
ABSTRACT Earnings management is an action taken by a manager in a company to manage profits in the company. The study in this case aims to analyze the factors that influence earnings management. This research is expected to provide prospective investors with more information about the factors that affect earnings management in companies that will be invested in capital. The population in this study is the food beverage sub-sector company which was listed on the Indonesia Stock Exchange in 2015-2018. The sampling technique in this study used purposive sampling and obtained a sample of 12 companies. The analytical method used is multiple linear regression analysis using SPSS 20. The results of the data analysis show that leverage affects earnings management while company size, company age, profitability, and business risk do not affect earnings management. Keywords : Company Size, Levereage, Company Age, Profitability, Business Risk, Profit Management